An ecological model of bridging the digital divide in education: A case study of OLPC deployment in Nepal. Issue 2 (30th January 2018) - Thapa, Devinder; Sein, Maung K.
Abstract: Techno‐centric initiatives to bridge the digital divide, such as One Laptop per Child (OLPC), has been criticized for not taking a holistic approach that has led to limited success in providing quality education in developing countries. Particular emphasis is placed on examining the context in Information and communication technology for development (ICTD) initiatives. In this paper, we applied the theoretical lens of information ecology to conceptualize context to conduct a case study of Open Learning Exchange Nepal, which has been described as one of the few successes in implementing OLPC. Our findings show that it is not the technology per se (OLPC in this case), but its ecosystem that brought quality education in schools of remote mountain regions of Nepal.